PENDETEKSIAN FINANCIAL STATEMENT FRAUD DENGAN BENEISH M-SCORE RATIO PADA PERUSAHAAN BARANG KONSUMSI - Queenny Lie; Joselin Lai; Serena Arief; Henny Ny; Namira Ufrida Rahmi (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2020)
Fraud of financial statements is intentional misstatement or disclosure with the intention of deceiving the users of the report with the aim of benefiting a party. Detection of financial statement fraud does not always get a bright spot due to various underlying factors and many methods to conduct financial statement fraud. One way to measure fraudulent financial statements is the Beneish M-Score Ratio. Beneish M-Score can be calculated using eight ratios, namely from DSRI, GMI, AQI, SGI, DEPI, SGAI, TATA, and LVGI. The purpose of this study was to examine and analyze the influence of DSRI, GMI, AQI, SGI, DEPI, SGAI, TATA, and LVGI on fraudulent financial statements in consumer goods companies listed on the Indonesia Stock Exchange for the 2014-2017 period. The theories used in this study are theories relating to DSRI, GMI, AQI, SGI, DEPI, SGAI, TATA, and LVGI. The type of research used is descriptive statistics with a quantitative approach. The method of data collection is a documentation study method with a logistic regression analysis method. The population used is the financial statements of consumer goods companies listed on the Indonesia stock exchange in 2014-2017. The sampling technique uses purposive sampling method. The results showed that simultaneously DSRI, GMI, AQI, SGI, DEPI, SGAI, TATA, and LVGI had an effect on detecting fraud. Partially GMI, DEPI has no effect on fraud detection. DSRI, AQI, SGI, SGAI, TATA, LVGI affect the detection of fraud.